APLIKASI SISTEM PENDUKUNG KEPUTUSAN UNTUK PEREKRUTAN KARYAWAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI PT BANGKIT MAKMUR ABADI PURBALINGGA - Dani Heriyanto; Uning Lestari; Dina Andayati (Jurnal SCRIPT, 2015)
ABSTRACT The process of recruitment is an important element in a company, because employees will act as the person who will carry out production activities. The more qualified employees in a company, then it will increase the maximum work. The process of hiring employees to still use manual way is by using Microsoft Excel. And for all this time the recruitment process is less objective, so requiring a system that is able to help and support in making decisions. This application is designed using Unified Modeling Language (UML) using the programming language Hypertext Processor (PHP), and the MySQL database and use the Decision Support System with Simple Additive weighting method (SAW) to produce a decision. The results of this system will be emphasized on the way of decision making. The use of a decision support system application using Simple Additive weighting method (SAW) on the recruitment system is able to provide a solution or the best alternative based on the highest ratings.